Numerical and experimental study on improving temperature uniformity of solar furnaces for materials processing. (May 2015) - Li, B.; Oliveira, F.A.C.; Rodríguez, J.; Fernandes, J.C.; Rosa, L.G.
Highlights: A novel approach based on heating by indirect irradiation has been developed. Two receiver materials (stainless steel and MoSi2 ) and 3 configurations were studied. Temperature control within ±5 °C at key spots was achieved up to 800 °C. Thermal model has been validated by comparison with measured data from thermocouples. Useful information is drawn for improving the design of new indirect heating setups. Abstract: Numerical simulation and experimental study of new type test setup based on the indirect irradiation are presented. The objective is to develop new technical ways to improve the temperature control and homogeneity conditions in reaction chambers for materials processing in solar furnaces. The finite element analysis package ABAQUS was used for heat transfer analysis (including conduction, radiation and convection in the thermal model) and K type thermocouples were installed for measuring temperatures at key spots in the test setup. The tests were conducted at a solar furnace of PSA (Plataforma Solar de Almería), where it was demonstrated that temperatures at key spots of the new test setup can be controlled in an accurate fashion by adjusting the openness of the shutter. For example, the desired temperature 800 °C can be controlled within the range ±5 °C. In order to understand the influencing factors for temperature control and uniformity, two receiver materials (stainless steel AISI 310 and molybdenum disilicide MoSi2 ) and three configurations were studied and the results are compared in this work. It is shown that the thermal model developed in this research is capable of predicting the thermal performance of the test setup and good agreement was shown by comparison with experimental results. Useful information can be drawn from the present study for improving the design of new type solar furnace based on indirect irradiation for high temperature materials processing.